Summarizing through the lens of cognitive load theory. : Implications for education and teaching methods - Piu, Angela; Angelini, Cinzia (Graphos. Rivista internazionale di pedagogia e didattica della scrittura, 2025)
Recognizing the complex and specific nature of summarizing, as well as its critical importance in education, necessitates the implementation of appropriate and targeted teaching-learning trajectories to develop summarizing abilities. This paper draws from an in-depth analysis of research grounded in cognitive load theory – which sheds light on the capacities and constraints of human cognitive architecture – to examine the learning mechanisms and information processing involved in summarizing. We outline the implications of this theoretical framework for educational and school settings, addressing both the design of a comprehensive teaching-learning path for developing summarizing skills and the identification of the most effective teaching-learning strategies and instructional materials for such a path.